1975
DOI: 10.1126/science.190.4216.804
|View full text |Cite
|
Sign up to set email alerts
|

Host Tree Location Behavior of a Tropical Vine ( Monstera gigantea ) by Skototropism

Abstract: From a previous study (4) we know that building hornets destrox or abandon cells whose direction thc did not determine and construct new cells aiccording to their own judgment. So far as thickness of cell walls is concerned, thcre is no difTcrence in construction bv juvenile and adult hornets. In fact, hb the timc thev start building, juvenile hornets aIre of the sanme age as adult hornets and continue building in the snime direction lor the r'st of thcir building period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 3 publications
0
69
1
Order By: Relevance
“…Monstera gigantean (Strong and Ray 1975). A photomorphogenic response, hook opening and circumnutating, and induction of twining by blue light and FR light in Cuscuta were described in the past (Lane and Kasperbauer 1965) and later confirmed (Orr et al 1996a(Orr et al , 1996b).…”
Section: Parasite Strategy Of Cuscutamentioning
confidence: 93%
“…Monstera gigantean (Strong and Ray 1975). A photomorphogenic response, hook opening and circumnutating, and induction of twining by blue light and FR light in Cuscuta were described in the past (Lane and Kasperbauer 1965) and later confirmed (Orr et al 1996a(Orr et al , 1996b).…”
Section: Parasite Strategy Of Cuscutamentioning
confidence: 93%
“…About 49 % of all aroids are secondary hemiepiphytes and posses distinctive characteristics when compared with other life forms. It was in these hemiepiphytes that Strong & Ray (1975) found skototropism, and Moodie (1976) reported production of heat during anthesis. We have also found that M. acuminata has one of the highest root pressures yet reported.…”
Section: mentioning
confidence: 99%
“…The genus Monstera (Araceae) comprises 22 species distributed in the neotropics (Madison, 1977b). In Monstera gigantea (M. tenuis or M. dubia according to Madison, 1977b), the juvenile prostrate herb ' searches ' for vertical substrates to climb by means of skototropism, growth towards the darker areas (Strong & Ray, 1975). In this genus, adventitious anchoring roots hold the appressed climber (Croat, 1988) to the bark of the host tree.…”
mentioning
confidence: 99%
“…It is also possible that flagellar growth is initiated in those resource-rich stems that can afford to inititate vegetative expansion. In flagellar stems originating from older stems I did not observe skototropic (towards dark) growth (Strong and Ray 1975).…”
Section: Plastic Vegetative Growth: Flagellar Shoots and Climbing Shootsmentioning
confidence: 93%